Rapid Prototyping 30 Model for PIV: Application in Human Trachea Model Flow Analysis - Mohd Salleh, Zuliazura; Osman, Kahar; Marian, Mohd Fairuz; Mat Hassan, Nik Normunira; Madon, Rais Hanizam; Samiran, Nor Afzanizam; Rashid, Razlin Abd; lshak, lzuan Amin; Darlis, Nofrizalidris (Penerbit Akademia Baru, 2021)
Experimental works for analysing flow behaviour inside human trachea has become continuous problem as the model used to study cannot imitate the real geometry of human trachea structure. As the technology develop, Rapid Prototyping (RP) become more useful in constructing the 3D model that has complexity in their geometries. RP not only offer several technologies in developing the 3D model, but also varies type of materials that can be used to manufacture the 3D model. In this study, RP technique was chosen to develop the 3D model of human trachea to do the Particle Image Velocimetry (PIV) experimental works. Material used was Vero Clear due to PIV need a model that transparent so that visualization on flow inside the model can be seen and the velocity magnitude can be capture. The geometry was adapted from 60 years old trachea patient where the images of trachea was taken by using CT-scan. MIMICS software was used to extracted the images before reconstruct the trachea into 3D model. Velocity distribution was visualized and the magnitude were taken at both left and right bronchi. From the analysis, it concluded that the distribution of airflow to the second generation of trachea was 60:40 to right and left bronchi. It follows the rules as the right bronchi need to supply more air to the right lung compared to left as the volume of right lung bigger that left lung.